From cyberspace to mindspace: A freudian psychoanalytic perspective on digital literacy - Ganggi, Roro Isyawati Permata; Maftuh Dadang Setiana; Budiyanti, Rani Tiyas (Record and Library Journal, 2025)
Background of the study: The response of members of the motorcycle community in Semarang to social media is in the spotlight because it triggers brawls. A person's ability to respond to digital information is interesting to study from two sides: the information science side, which focuses on digital literacy, and the psychology side, which uses the Freudian psychoanalytic approach. Purpose: A more profound investigation is required to ascertain the Freudian psychoanalytic perspective on digital literacy of the motorcycle community in Semarang. Method: Qualitative research with a phenomenological approach was selected to investigate the experiences of motorcycle community members in Semarang regarding digital literacy. Data were gathered through interviews, observations, and document analysis. This research involved six informants who are members of the motorcycle community in Semarang. Findings: The relationship between psychoanalysis and digital literacy can be utilized to gain insight into the Freudian psychoanalytic perspective on digital literacy within the motorcycle community in Semarang. One of the critical areas of study in Freudian psychoanalysis is the development of an individual's cognitive processes. As observed through psychoanalytic lenses, the digital literacy abilities of motorcycle community members in Semarang can be understood based on three fundamental elements: the id, ego, and superego. Conclusion: A complex array of internal and external factors shapes the digital literacy behavior of the motorcycle community in Semarang. The internal elements are primarily influenced by Freudian psychoanalysis, which posits the existence of three fundamental psychological drives: the id, ego, and superego. In contrast, external elements are shaped by mind space, which encompasses both cognitive processes and environmental factors. These two domains collectively influence an individual's behavior, thought patterns, and decision-making abilities.